2021
DOI: 10.1007/s00701-021-04992-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of an intracranial multimodal monitoring bolt system for neurocritical care: a single-center experience

Abstract: BackgroundIntracranial multimodality monitoring (iMMM) is increasingly used in acute brain injured patients; however, safety and reliability remain major concerns to its routine implementation. MethodsWe performed a retrospective study including all patients undergoing iMMM at a single European center between July 2016 and January 2020. Brain tissue oxygenation probe (PbtO 2 ), alone or in combination with a microdialysis catheter and/or an 8-contact depth EEG electrode, was inserted using a triple lumen bolt … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the most extensive series (501 patients), Bailey et al [8] reported only one infection due to an improper bolt placement technique with a faulty seal causing a CSF leak and potentially bacterial meningitis. Al Barajraji et al [16] reported that nine (8%) of their patients developed CNS infections. However, despite a relatively high mean monitoring time, they did not attribute it to iMMM; no intraventricular misplacement was associated with CNS infections [16].…”
Section: Cns Infectionsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the most extensive series (501 patients), Bailey et al [8] reported only one infection due to an improper bolt placement technique with a faulty seal causing a CSF leak and potentially bacterial meningitis. Al Barajraji et al [16] reported that nine (8%) of their patients developed CNS infections. However, despite a relatively high mean monitoring time, they did not attribute it to iMMM; no intraventricular misplacement was associated with CNS infections [16].…”
Section: Cns Infectionsmentioning
confidence: 98%
“…Forty-one iMMM dislodgements with rates of 5.7% and 7.8% and six breakings with rates of 1.62% and 3.88% were retrieved from series by Al Barajraji et al [16] and Dings et al [17]. Stuart et al [14] and Foreman et al [7] reported that inadvertent monitoring discontinuation occurred for 43% and 58% of their patients, respectively.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…An eight-contact dEEG electrode (Dixi Medical, Besançon, France) was placed via a bolt system in patients with ABI by a neurosurgeon in the operating room. A detailed description of the surgical procedure of dEEG was published in our previous article [10]. Briefly, the dEEG electrode was positioned 1.5 cm anteriorly from Kocher's point, targeting the frontal lobe of the injured side or in the case of surgical constraints (i.e., large craniectomy, large intracranial hematoma, hydrocephalus) in the contralateral side.…”
Section: Deeg Surgical Proceduresmentioning
confidence: 99%
“…In a previous study, we demonstrated that the implementation of an eight‐contact dEEG electrode inserted using a triple‐lumen bolt system was safe [10]. In this study, we aimed to explore the concordance between electrophysiological activities displayed on dEEG and those on scEEG in patients with ABI.…”
Section: Introductionmentioning
confidence: 99%